Chromium carbide/Carbon Nanotube Hybrid Structure Assisted Copper Composites with Low Temperature Coefficient of Resistance. Issue 1 (December 2017) - Cho, Seungchan; Kikuchi, Keiko; Lee, Eunkyung; Choi, Moonhee; Jo, Ilguk; Lee, Sang-Bok; Lee, Sang-Kwan; Kawasaki, Akira
Abstract In order to explore the possibility of using carbon nanotube (CNT) to introduce and control the temperature coefficient of resistance (TCR) of metal matrix composite, relatively thick and short multi-walled CNTs (MWCNTs) were introduced in the metal matrix within-situ formation of chromium carbide (Cr7 C3 ) at the CNT/copper (Cu) interface. We demonstrate that incompatible properties such as electrical conductivity and TCR can be achieved simultaneously by introducing MWCNTs in the Cu matrix, with control of the interfacial resistivity using the MWCNT/Cr7 C3 –Cu system. High electrical conductivity of 94.66 IACS and low TCR of 1, 451 10–6 °C−1 are achieved in the 5 vol.% MWCNT–CuCr composite.In-situ formation of Cr7 C3 nanostructures at the MWCNT/Cu interface by reaction of diffused Cr atoms and amorphous carbon of MWCNTs would assist in improving the electrical properties of the MWCNT–CuCr composites.